Problem ubóstwa w polityce zrównoważonego rozwoju - Lorek, Agnieszka (Poverty problem in the sustainable development policy, 2007)
The Millennium Development Goals are the most comprehensive and widely supported set of poverty reduction targets the world has ever established. Without access to adeąuate education, health care, and safe drinking water, people’s capacity to realize their own potential as productive workers, informed members of their communities and fulfilled individuals is constrained. The intemational community’s strong support for the MDGs has generated considerable pressure to incorporate them into national programmes of aid-recipient countries and aid programmes of bilateral and multilateral donors. It is elear that not all countries will follow the same path toward reaching the Millennium Development Goals. Accelerating global progress will require additional resources but, just as important, eąuitable policies and institutions to absorb and use those resources effectively are also needed, both nationally and intemationally. Attaining the Goals will represent significant movement toward a morę eąuitable and prosperous world.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 146-157